2014
DOI: 10.1111/bdi.12181
|View full text |Cite
|
Sign up to set email alerts
|

Brain regions associated with risk and resistance for bipolar I disorder: a voxel‐based MRI study of patients with bipolar disorder and their healthy siblings

Abstract: The results of this study suggest that a reduction in the volume of the orbitofrontal cortex, which plays a role in the automatic regulation of emotions and is a part of the medial prefrontal network, is associated with the heritability of bipolar disorder. Conversely, increased dorsolateral prefrontal cortex volume may be a neural marker of a resistance factor as it is part of a network of voluntary emotion regulation and balances the effects of the disrupted automatic emotion regulation system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 47 publications
1
39
1
Order By: Relevance
“…Kempton et al reported that the genetic predisposition to bipolar disorder was associated with increased left insula volume [42], whereas Matsuo et al indicated an association with the right insula [43]. In addition to these reports, a recent, more carefully designed study conducted with unaffected healthy siblings of patients with bipolar disorder suggested that a reduction in the volume of the orbitofrontal cortex is associated with the heritability of bipolar disorder [44]. This suggestion is partially consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Kempton et al reported that the genetic predisposition to bipolar disorder was associated with increased left insula volume [42], whereas Matsuo et al indicated an association with the right insula [43]. In addition to these reports, a recent, more carefully designed study conducted with unaffected healthy siblings of patients with bipolar disorder suggested that a reduction in the volume of the orbitofrontal cortex is associated with the heritability of bipolar disorder [44]. This suggestion is partially consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Structural changes in the cerebellum have also been reported in healthy relatives of BD patients. In these high-risk design VBM studies, increased vermal volume in healthy relatives of BD patients was considered as a resilience marker (Kempton et al, 2009;Frangou, 2012), whereas decreased cerebellar volume found both in healthy siblings and bipolar patients in comparison to controls was interpreted as a vulnerability marker (Eker et al, 2014). Taken together, our finding of decreased cerebellar (vermal) volume in bipolar patients and first-degree relatives might be associated with genetic vulnerability for bipolar disorder.…”
Section: Discussionmentioning
confidence: 67%
“…In addition to functional neuroimaging studies, structural changes in the IFG of bipolar patients were repeatedly reported in previous VBM studies. Several studies found smaller GM density in the right IFG in BD patients with a chronic illness course (Eker et al, 2014;Lyoo et al, 2004;Stanfield et al, 2009), whereas no change in GM volume of the ventrolateral prefrontal cortex was observed in the first-episode BD patients compared to controls (Adler et al, 2007). Furthermore, smaller IFG volumes have been reported in multiepisode BD patients in comparison to first-episode BD patients .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MRI and fMRI studies have indicated that bipolar disorder patients have a significant increase in white matter hyperintensities and a decrease in volumes of the dorsolateral prefrontal cortex (DLPFC) as well as orbitofrontal cortex which overlaps with the ventromedial prefrontal cortex (VMPFC), possibly resulting from hyperactivity of these brain regions (Pillai et al, 2002;Zald & Andreotti, 2010;Eker et al, 2014). DLPFC activity is significantly decreased in response to emotional stimuli in euthymic bipolar patients compared with healthy individuals in an fMRI study (Hassel et al, 2008).…”
Section: Neuroinflammation In the Amygdala And Neural Network Abnormamentioning
confidence: 99%